KUALITAS PELAYANAN PUSKESMAS PATUMBAK DALAM MENINGKATKAN KEPUASAN MASYARAKAT DI KECAMATAN PATUMBAK KABUPATEN DELI SERDANG - Gangga Sembiring, Fransiskus Triananda; Winaya, I Ketut; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
Health become basic rights for society in a country.The service quality rendered must also be observed by the agency because this can give patients confidence in health service so that a sense of satisfication arises in public. On the other hand, public satisfication is a measure of the quality of services rendered by such agencies. This research used a qualitive descriptive method with data gathered by observation, interviews and documentation. The result of this research shows that Service Quality of The Patumbak Public Health Center to Increase public satisfication is not yet fully effective because public still compaints about some indicator which is there was no employee in Patumbak Public Health Center on the spot during office hours, employee less friendly to the patients, and also security on the inside of the building nor outside of the building doesn’t optimum Keyword : Service Quality, Public Health, Public Satisfication